2017
DOI: 10.1785/0120150253
|View full text |Cite
|
Sign up to set email alerts
|

Local Earthquake Magnitude Scale andb‐Value for the Danakil Region of Northern Afar

Abstract: The Danakil region of northern Afar is an area of ongoing seismic and volcanic activity caused by the final stages of continental breakup. To improve the quantification of seismicity, we developed a calibrated local earthquake magnitude scale. The accurate calculation of earthquake magnitudes allows the estimation of b-values and maximum magnitudes, both of which are essential for seismic-hazard analysis. Earthquake data collected between February 2011 and February 2013 on 11 three-component broadband seismome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…This distribution in seismicity implies that faulting in the Danakil Depression accommodates a larger proportion of extension than elsewhere in Afar. Additionally, local seismicity recorded in the Danakil during 2011-2013 shows that the in-rift fault system near Dallol is seismically active (Illsley-Kemp et al, 2017), consistent with the view that the role of magmatism in achieving extension here is reduced. To facilitate mechanical upper crustal extension and rapid basin subsidence, it is likely that contemporaneous ductile stretching of the lower crust and mantle lithosphere has occurred; this would explain the marked thinning of the crust in Danakil (~15 km) compared to elsewhere in Afar (~25 km; (Eagles et al, 2002).…”
Section: Formation Of the Danakil Depressionsupporting
confidence: 72%
“…This distribution in seismicity implies that faulting in the Danakil Depression accommodates a larger proportion of extension than elsewhere in Afar. Additionally, local seismicity recorded in the Danakil during 2011-2013 shows that the in-rift fault system near Dallol is seismically active (Illsley-Kemp et al, 2017), consistent with the view that the role of magmatism in achieving extension here is reduced. To facilitate mechanical upper crustal extension and rapid basin subsidence, it is likely that contemporaneous ductile stretching of the lower crust and mantle lithosphere has occurred; this would explain the marked thinning of the crust in Danakil (~15 km) compared to elsewhere in Afar (~25 km; (Eagles et al, 2002).…”
Section: Formation Of the Danakil Depressionsupporting
confidence: 72%
“…The b ‐value of 0.87 ± 0.03 estimated for the Magadi‐Natron‐Manyara rift zone is identical to the b ‐value of 0.87 for the central Kenya rift [ Tongue et al ., ], and similar to the b ‐value of 0.84 for Tanzania, which includes the Archaean craton [ Langston et al ., ], and 0.9 for the intensely intruded and faulted Danakil Depression [ Illsley‐Kemp et al ., ] (supporting information Figure SM1). A large number of earthquakes occurred south of our array in the Manyara basin where Albaric et al .…”
Section: Resultsmentioning
confidence: 99%
“…[] estimate an unusually low b ‐value of 0.77 for a 7 month time period of observation in the Magadi basin, which included an intense swarm interpreted as a dike intrusion. Inclusion of events from the 1989 Magadi swarm may explain the apparent temporal variations between the two studies, as has been observed in other magmatically active zones [e.g., Wiemer et al ., ; Illsley‐Kemp et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4,971 earthquakes of magnitude 0.4–5.8 was recorded during the experiment and was located with a 2‐D velocity model (Hammond et al, ; Lomax et al, ; Makris & Ginzburg, ). These earthquakes have average location errors of ±1.9 km and ±4.1 km in the horizontal and vertical directions, respectively, and the catalogue is complete above magnitude 2.0 (Illsley‐Kemp et al, ). Generally, earthquakes are focused at the western rift margin, which separates the Ethiopian plateau from the Afar depression, or in the vicinity of volcanic centers (Illsley‐Kemp et al, ; Figure ).…”
Section: Observational Methods and Resultsmentioning
confidence: 99%